2001
DOI: 10.1161/hy1001.092613
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Target Organ Damage in Hypertensive Blacks and Whites

Abstract: Abstract-The purpose of this study was to evaluate the association of the insulin resistance syndrome with both blood pressure and target organ damage in blacks and whites with essential hypertension. Eighty-two black and 63 white French Canadian patients were studied. None had diabetes, and antihypertensive medications had been discontinued for Ն1 week. Key Words: hypertrophy Ⅲ glomerular filtration rate Ⅲ insulin resistance Ⅲ microalbumin Ⅲ race Ⅲ target organ damage R esistance to insulin-stimulated glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 59 publications
1
19
1
1
Order By: Relevance
“…Higher renal risk in Africans has been documented by other researchers. 14,32 However, in the current study, ROC-developed WC cut-off points were not associated with ACR. This may imply that the albumin to creatinine ratio is not the best measurement of kidney dysfunction, and that the estimated glomerular filtration rate should rather be applied where different grades of renal function need to be assessed, independent of ethnicity and gender.…”
Section: Mencontrasting
confidence: 71%
See 1 more Smart Citation
“…Higher renal risk in Africans has been documented by other researchers. 14,32 However, in the current study, ROC-developed WC cut-off points were not associated with ACR. This may imply that the albumin to creatinine ratio is not the best measurement of kidney dysfunction, and that the estimated glomerular filtration rate should rather be applied where different grades of renal function need to be assessed, independent of ethnicity and gender.…”
Section: Mencontrasting
confidence: 71%
“…10 MetS can contribute to the strain of microalbuminuria as a marker of target organ damage. 8,9,[11][12][13][14] It has been found that various MetS risk factors have been associated with renal impairment with regard to target organ damage in the SABPA population. 8,15 Determining ethnic-, gender-, and age-specific waist circumference cut-off points to predict metabolic syndrome: the Sympathetic Activity and Ambulatory Blood Pressure in Africans (SABPA) study JEMDSA The aim of this study was firstly to develop a WC cutoff point for Africans and Caucasians in ethnic-, gender-and age-specific groups (25-45 years and 46-65 years) for MetS in this cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Although no previous study has demonstrated detrimental outcomes associated with higher GFR among patients with atherosclerotic cardiovascular disease, previous investigations have suggested that an elevated GFR is associated with other target organ damage (18,19). For example, among 111 hypertensive subjects with normal renal function, glomerular hyperfiltration was associated with the presence of left ventricular hypertrophy, after adjustment for age, BMI, body surface area, and arterial pressure (19).…”
Section: Discussionmentioning
confidence: 99%
“…For example, among 111 hypertensive subjects with normal renal function, glomerular hyperfiltration was associated with the presence of left ventricular hypertrophy, after adjustment for age, BMI, body surface area, and arterial pressure (19). The presence of cardiac hypertrophy, glomerular hyperfiltration, and sodium retention has particularly been noted among black subjects with hypertension (18). In addition, studies have suggested that the presence of glomerular hyperfiltration in subjects with hypertension and diabetes increases a patient's risk for progressive renal dysfunction (20 -24).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a large number of cross-sectional studies in hypertensive subjects have established an almost constant association between nocturnal BP phenotypes with cardiac adaptations including abnormal LV mass and geometry. 7,8,12,21,22 In addition, nondippers and those with hypertensive nocturnal BP values demonstrated impaired LV diastolic function, abnormal aortic root diameters and left atrium structural properties compared with dippers and those with normotensive nocturnal BP levels, respectively. 23,24 However, other studies have reported no difference in cardiac adaptations among dippers and nondippers, [25][26][27][28] whereas nocturnal hypertension was constantly related to LV mass, an issue not addressed by absolute nocturnal systolic and diastolic BP.…”
Section: Cardiac Adaptationsmentioning
confidence: 97%